Overspinning problem in Kerr black holes: second order corrections and self-energy - Iván R. Vásquez (European Physical Journal C: Particles and Fields)
Abstract We consider gedanken experiments to destroy Kerr black holes, by means of absorbing matter with sufficient energy and angular momentum. It is shown that extremal and near-extremal Kerr black holes cannot be destroyed in a process that includes a second order contribution to its final mass, and matter sources satisfy the null energy condition. Such contribution is calculated using hypersurface integration on the event horizon, and it traces similarities with terms related to matter-black hole interactions and a rotational self-energy lower bound suggested in previous works.